Physical Mapping of a Novel Locus Conferring Leaf Rust Resistance on the Long Arm of Agropyron cristatum Chromosome 2P - Jiang, Bo; Liu, Taiguo; Li, Huanhuan; Han, Haiming; Li, Lihui; Zhang, Jinpeng; Yang, Xinming; Zhou, Shenghui; Li, Xiuquan; Liu, Weihua (Frontiers in Plant Science, 2018)
Wheat leaf rust is one of the most common wheat diseases worldwide and can cause up to 40% wheat yield loss. To combat the growth and spread of leaf rust disease, continual exploration and identification of new and effective resistance genes are needed. Here, we report for the first time a locus conferring leaf rust resistance located on the long arm of Agropyron cristatum chromosome 2P in Triticum aestivum-A. cristatum 2P translocation lines. This study used 50 leaf rust races, including two Chinese major dominant leaf rust races, named by THT and PHT, and other 48 different leaf rust races collected from 11 provinces, 1autonomous region and 1 municipality of China to test the resistance to T. aestivum-A. cristatum 2P chromosome translocation lines and their backcross populations, the results indicated that the novel leaf rust resistance locus was immune or nearly immune to all tested leaf rust races. Four long arm translocation lines with different breakpoints of A. cristatum chromosome 2PL and their backcross populations were tested with leaf rust race THT at the seedling and adult stages and genotyped with 2P-specific STS markers. The results showed that the novel leaf rust resistance locus of the T. aestivum-A. cristatum 2P translocation lines was located in the chromosomal bin FL 0.66-0.86 of 2PL. Therefore, T. aestivum-A. cristatum 2P chromosome translocation lines conferring leaf rust resistance locus could provide a novel disease-resistance resource for future wheat breeding programs.